Thrombolysis in Arterial Occlusion - Verhaeghe, Raymond (Thrombosis and Haemostasis, 1999)
Intra-arterial thrombolytic therapy has replaced systemic intravenous infusion of thrombolytic agents as a treatment modality for arterial occlusion in the limbs. Several catheter-guided techniques and various infusion methods and schemes have been developed. At present there is no scientific proof of definite superiority of any agent in terms of efficacy or safety but clinical practice favours the use of urokinase or alteplase. Studies which compared thrombolysis to surgical intervention suggest that thrombolytic therapy is an appropriate initial management in patients with acute occlusion of a native leg artery or a bypass graft. Underlying causative lesions are treated in a second step by endovascular or open surgical techniques. Severe bleeding is the most feared complication: the risk of hemorrhagic stroke is 1-2%.
Keywords: Thrombolytic therapy; arterial occlusion; acute ischemia; vascular surgery